Collective memory of umbilical cord stump care: an educational experience - Eliane Fonseca Linhares; Joana Angélica Andrade Dias; Maria da Conceição Quirino dos Santos; Rita Narriman Silva de Oliveira Boery; Ninalva de Andrade Santos; Felipe Eduardo Ferreira Marta
ABSTRACT Objective: To report the educational experience with pregnant women considering the recovery of collective memory inherited from the care for the umbilical cord stump provided by grandmothers. Method: This case study was based on collective memory and resulted from a workshop with 20 pregnant women from a Basic Health Unit in a city in the inland of Bahia. Results: The study showed that pregnant women's grandmothers are significant in the stump care process because they transmit their memories pervaded by beliefs, myths and superstitions that, although should be respected by nurses and other health professionals, can sometimes contribute to the occurrence of omphalitis and neonatal tetanus. Final considerations: The results indicated the need for raising awareness and education of all persons involved in this care, especially grandmothers, so that they can reflect on the risks and damage that certain empirical knowledge can cause to the health of the umbilical cord.